Superlubricidade no deslizamento de cerâmicos lubrificados com água - Strey, Nathan Fantecelle (2019)
Superlubricity is the state of a tribosystem characterized by extremely low friction coefficients, with μ < 0.01. The superlubricity of ceramic pairs sliding in water has been reported for several similar and dissimilar tribopairs: Si3N4-Si3N4; SiC-SiC, Al2O3-Al2O3, ZrO2-ZrO2, Si3N4-SiC, Si3N4 Al2O3, Al2O3-SiC, ZrO2-SiC, etc. By hypothesis, some requirements must be satisfied for superlubricity in these tribosystems to occur: low enough mean contact pressure, adequate surface finish, a mild wear regime during running-in where tribochemical mechanisms are dominant, and formation of a soft tribofilm adhered to surfaces. These conditions were reevaluated through different approaches: (i) the polishing process parameters were optimized during the preparation of engineering ceramics used in tribological components and a better surface finish was obtained for SiC surfaces when compared to Al2O3 or ZTA ones; (ii) wear maps were developed for several dissimilar ceramics pair sliding in water which showed that the combination of tribologically compatible ceramic counterparts extends the operating conditions range of ceramic sliding bearings and that the mild wear regime is a necessary but not sufficient condition for the occurrence of superlubricity. Finally, (iii) the construction of Stribeck curves for Si3N4-SiC, ZrO2-SiC, Si3N4-Al2O3 and SiO2-SiO2 pairs showed that superlubricity is associated with mixed or hydrodynamic lubrication regime, depending on operating conditions, and that the ratio between the minimum thickness of the hydrodynamic film and the amplitude of the surface roughness peaks (λ ratio) is the parameter that best explains the friction coefficient of these tribosystems.